SURAKARTA: PERKEMBANGAN KOTA SEBAGAI AKIBAT PENGARUH PERUBAHAN SOSIAL PADA BEKAS IBUKOTA KERAJAAN DI JAWA - Suci Nur Aini Zaida; Nurhayati HS Arifin (http://arl.faperta.ipb.ac.id/, 2010)
The aim of this study was to describe the relation of urban landscape development that influenced by social change. This study was focused on the changing occur before the Kingdom of Surakarta untilreformation period. The analysis was intended to find out the main factors that had been influencing the urban landscape development and also to formulate the concept of urban planning in the future based on its history and thesocial character.Surakarta, otherwise Solo or Salay, was the capitalcity of Surakarta Hadiningrat's Kingdom. Founded in 1745, it was built on a magical rather than a rational consideration. It’s located in the crosscurrent of two rivers, the Bengawan Solo and the Pepe. According to the Javanese cosmology, the inner city comprised of the kraton complex called Baluwarti and the alun-alun (palace square), all located inside the beteng (palace wall). Outside the palace wall were houses of the sentana (nobility), the abdi dalem (retainers) and the commonners. The coming of the Europeans, the Chinese and the Arabs formerly did not alter the cosmology concept of the city. Inthe beginning of the twentieth century, due to the advance of technology and the expansion of business, service and leisure, the city was changed. It was in development period that the most change towards a modern city took place. The skeleton of the city remained the same, but the environment became entirely different.